Term Structure of Interest Rates. Emergence of Power Laws and Scaling Laws - Thomas Alderweireld; Jean Nuyts (Economics and Econometrics Research Institute (EERI), 2003)
The technique of Padé Approximants, introduced in a previous work, is applied to extended recent data on the distribution of variations of interest rates compiled by the Federal Reserve System in the US. It is shown that new power laws and new scaling laws emerge for any maturity not only as a function of the Lag but also as a function of the average inital rate. This is especially true for the one year maturity where critical forms and critical exponents are obtained. This suggests future work in the direction of constructing a theory of variations of interest rates at a more ''microscopic'' level.
Keywords: B23; C51; 330; Interest rates scaling laws